A content analysis of cross-cultural motivational studies in tourism relating to nationalities. (March 2019) - Soldatenko, Daria; Backer, Elisa
Abstract: The importance of outbound markets to a host country has increased scholars' interest in understanding motivational factors. Motivation is a basic determinant of tourists' behaviour and has a fundamental role in tourism. The awareness of motivational differences among tourists from main generating markets is a prerequisite for effective and successful destination marketing programs. However, cross-cultural motivation comparisons of tourists from different cultural backgrounds has received relatively little research attention. In addition, there has not been a content analysis undertaken on this topic. Therefore, the aim of this research was to examine and synthesise previous studies on cross-cultural tourist motivation comparison, reveal the gaps in the literature and indicate the future research trends. A review of 71 publications covering a period of 30 years, from 1988 to 2017, was conducted. This study focuses on both subject areas and research methods used. The findings of this content analysis identified a recent growth in cross-cultural comparison studies. The analysis also revealed an increase in more advanced analysis including multiple variables such as motivations, satisfaction, segmentation of visitors, intention behaviours, and information search behaviour. The analysis of nationalities compared in the reviewed studies indicated the shift of research interest towards Asian countries. In the case of research methods, quantitative design is more common for cross-cultural motivation studies.